Pengembangan Video Pembelajaran Pada Materi Ikatan Kimia Untuk Mendukung Pembelajaran Daring Berbasis Advance Organizer - Niken Widyastuti; Riswandi; Helmy Fitriawan (Universitas Pancasakti Tegal, 2021)
The policy of learning from home due to the Covid 19 virus encourages teachers to create innovative learning media thatcan be accessed by students anywhere. Learning media is developed in accordance with learning objectives and studentneeds. The purpose of this research is to make learning videos to support advance organizer distance learning and tomeasure the attractiveness of learning videos that have been developed using the Dick and Carey model. The test subj ects inthis study were 39 students of class X of laboratory test analytical competence. Research instruments include observationsheets and interviews and attractiveness test questionnaires. The results of the attractiveness test showed a value of 3.45from a scale of 4.00. The conclusion of this research is that this learning video is attractive to use by students and supportadvance organizer distance learning